Natura, poesia e filosofia in Hölderlin e in Hegel (Studia theodisca, 2025)
The study addresses essential aspects of the works of Hölderlin and Hegel, highlighting the affinities and differences between the two with regard to their approach to pantheism, the question of beauty and the concept of ‘truth as a whole’. The essay also investigates differences and similarities in their interpretation of Heraclitus and the One-All, their conception of the tragic, their approach to the relationship between man and nature, and their aspiration for a genuine cultural, ethical, and political revolution. Finally, the essay delves into the differences between Hegel’s ‘logic’ and Hölderlin’s ‘poetic logic’, as well as the different paths the two great authors followed in their shared love for ‘free truth’.